An updated approach to incremental cycling tests: Accounting for internal mechanical power - Giorgi, H. P.; Andrews, M. H.; Gray, A. J.; Osborne, M. A. (Journal of Science and Cycling, 2015)
Incremental cycling tests are typically used to determine blood lactate thresholds to monitor training and to form the basis for prescribing training zones. With minimal additional post-processing of the data normally collected during these tests, a more comprehensive description of the flow of metabolic to mechanical energy could be developed. The aim of this study was to further analyse data collected during routine incremental testing to estimate the metabolic cost of internal mechanical power (IP) and to assess the flow of energy between the foot and the pedal to indicate the sharing of energy between IP and the external mechanical power (EP). Eight elite male cyclists completed three cycling incremental tests to exhaustion, beginning at 100 W and increasing by 50 W/5min, at cadences of 50-55, 80-85 and 110-115 rev/min Submaximal oxygen consumption values were converted to metabolic power (MP) and, together with external mechanical power (EP) values, were put into a physiological model for estimating IP. Mean crank power throughout the crank revolution was determined from the simultaneous collection of crank power data at each cadence and workload. There was a significant increase in IP as cadence increased: 11 ± 5 W, 33 ± 11 W and 70 ± 22 W for cadences of 50-55, 80-85 and 110-115 rev/min, respectively. Crank power increased as workload increased, and positive and negative crank powers were generally larger and smaller, respectively, as cadence increased. In addition to determining blood lactate thresholds, routine incremental cycling tests can be used to quantify the metabolic cost of IP and to help describe the flow of metabolic energy to its mechanical energy destinations, i.e., to EP and IP.